DEVELOPING TECHNOLOGY-BASED ARABIC LANGUAGE LEARNING MEDIA FOR THE DIGITAL GENERATION - Khalik, Muh. Fihris (Yayasan Adra Karima Hubbi, 2026)
The development of digital technology has significantly influenced the learning patterns and characteristics of the digital generation, including in the context of Arabic language learning. Traditional learning approaches, which are still one-way and limited to conventional media, are considered inadequate to meet the learning needs of today's students. This situation drives the need for innovation through the development of Arabic language learning media integrated with technology. This study aims to design technology-based Arabic language learning media that are appropriate to the characteristics of the digital generation and to evaluate the feasibility and effectiveness of their use in the learning process. The method applied is research and development (R&D), including the stages of needs analysis, media design, product development, expert validation, and limited trials on students. Data collection was conducted through questionnaires, observations, and learning outcome tests, while data analysis used descriptive quantitative and qualitative approaches. The results of the study indicate that the technology-based Arabic language learning media developed received a very good rating from material and media experts. Furthermore, the implementation of this media has been proven to increase student motivation and learning achievement. These findings confirm that the integration of technology in Arabic language learning media can create a more interactive, engaging, and relevant learning process to meet the needs of the digital generation.